2023
DOI: 10.1039/d3mh00780d
|View full text |Cite
|
Sign up to set email alerts
|

Origin and characterization of the oxygen loss phenomenon in the layered oxide cathodes of Li-ion batteries

Abstract: Li-ion batteries have been widely applied in the field of energy storage due to their high energy density and environmental friendliness. Attributing to the high capacity (~200 mAh g-1) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…This is generally related to O-loss which reduces the O content at the surface and triggers Ni migration inward to sites in the Li layer. 5,24,48–53 To quantify O-loss in our sample, operando electrochemical mass spectrometry (OEMS) was performed for LiNiO 2 over the first cycle, ESI† Fig. S9 and S10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is generally related to O-loss which reduces the O content at the surface and triggers Ni migration inward to sites in the Li layer. 5,24,48–53 To quantify O-loss in our sample, operando electrochemical mass spectrometry (OEMS) was performed for LiNiO 2 over the first cycle, ESI† Fig. S9 and S10.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research into O oxidation in Li-rich cathodes, such as Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 , has indicated that oxidised oxygen takes the form of molecular O 2 , which is trapped within vacancy clusters in the cathode structure. 21–25 However, in the case of stoichiometric materials like LiNiO 2 , it has been argued that this same mechanism cannot apply due to the lack of transition metal vacancies in the fully dense transition metal layers (in the Li-rich materials the Li in the transition metal layers are removed on charge and the remaining vacancies cluster to accommodate the O 2 ). 14,15…”
Section: Introductionmentioning
confidence: 99%